Nuclear abnormalities and Oxidative Stress Induced by Hookah (Shisha) in Male Human in Erbil City - Natheer Yaseen (College of Education for Pure Sciences, 2022)
Nowadays hookah smoking has dramatically increased especially in the Middle East. Because Hookah tobacco contains many harmful substances, it has dangerous impacts on human beings. The goal of the current study is to examine the oxidative stress in blood and clastogenic effects of hookah smoking on exfoliated buccal cells. One hundred and twenty five healthy adult males were involved in this study. The participants were distributed into five groups: control, passive smokers, and three hookah smoker groups. Samples of blood from all groups were examined for Malondialdehyde (MDA) level and exfoliated buccal cells were aslo examined thorough micronucleus (MN) test for frequencies of nuclear abnormalities including Micronucleus (MN), Binucleates (BN) and Karyolysis (KL), were evaluated as well. frequencies of all nuclear abnormalities Micronucleus (MN), Binucleates (BN) and Karyolysis significantly increased in all exposed groups compared to the control group and the effect was exposure duration dependent. Malondialdehyde level also significantly increased in all exposed groups compared to the control group and the effect was exposure duration dependent.